Digitization model for costs and operating times reduction in Peruvian Banks - Castro-Nagatomy, Eder (2022)
Deforestation is one of the problems that is producing a significant impact on the environment in countries that have large extensions of forests such as Peru, caused by different factors such as paper consumption, whose increase in recent years has also generated an increase in the costs and times related to the management and transportation of physical documents. These physical processes were further affected due to the COVID-19 restrictions, having a significant negative impact on customer satisfaction due to some processes that required their presence at bank branches. According to recent research, 90% of financial institutions continue to maintain a traditional document management system that consists of printing, storing and consulting physical documents, due to the lack of culture and activities aimed at digitizing processes; however, this change is possible with a model oriented to the transformation of said processes and the organizational culture; our main motivation to carry out this research was the change that the digitization of processes offers to companies and the environment. Our management model consists of 4 stages: collection of necessary requirements, identification of the main problem and improvement objectives, execution of the 3 management tools selected from our model and validation of the results obtained. The result obtained thanks to the application of the model in our validation case, shows a reduction of 65% of the costs related to document management in the first 3 months, in the following 3 months the reduction suffers an increase to 95.37%. In addition to this, the time to search and obtain documents will be reduced by approximately 99%. In conclusion, we determined that Change Management and Organizational and Infrastructure Management are necessary to be able to transform physical processes into digital ones since these three complement each other.